Imaginando el retorno de los vascos. Algunas reflexiones - Marcelino Irianni (Amnis)
If immigration involves dark and unfinished topics that are difficult to access, the most representative one is that about returns. At first sight it seems very simple and as the most part of other areas into the same topic, it has suffered changes in its questions and answers all over the last decades. The concept of the phenomenon that return means changed according to advances in theory, different ways of computing data and even new sources to get information.